Experimental measurement of the flow-induced pulsation in a hydrodynamic turbomachinery stator and its pressure fluctuation characteristics - Zhifang Ke; Wei Wei; Cheng Liu; Qingdong Yan; Houston Wood (Engineering Science and Technology, an International Journal, 2022)
By means of experimental measurement of the transient internal flow field and the periodic lumped-blade separation analysis method (PLSAM), the pressure field distribution on a stator blade surface and the corresponding flow-induced pulsation, as well as the fluctuation characteristics in a torque converter are acquired and further analysed. The results show that there are fluctuation characteristics in both the blade pressure distribution results and the blade torque under the influence of flow induced pulsation, while the relationship between these fluctuations and the rotatory angle of the wheels reveals the mechanism of the flow induced pulsation; namely, the main cause of the flow induced pulsation lies in the successive switching of the turbine/pump blade position relative to the stator, which can be modelled by a trigonometric function in both the space domain and time domain, while the frequency domain characteristics of this trigonometric function exist in both the internal flow characteristics and performance results, which allows a connection to be built between the macro-performance and the micro-internal flow character and can be used for the inverse design of the cascade system.